A novel sulfamoylphenyl-dihydro-thiadiazole derivative as a dual EGFR and carbonic anhydrase inhibitor for cancer therapy - Ibrahim H. Eissa; Hazem Elkady; Walid E. Elgammal; Hazem A. Mahdy; Dalal Z. Husein; Fatma G. Amin; Asmaa A. A. Elsheshiny; Shimaa. S. Abdelfattah; Aisha A. Alsfouk; Eslam B. Elkaeed; Ahmed M. Metwaly (PLoS ONE, 2025)
A novel sulfamoylphenyl-dihydro-thiadiazole derivative (compound 14) has been designed and synthesized as a dual inhibitor targeting EGFR and human carbonic anhydrases (hCA_IX and hCA_XII). Computational studies, including density functional theory (DFT), molecular docking, and molecular dynamics simulations, confirmed its stability, favorable binding interactions, and reactivity profiles. Compound 14 showed potent inhibition of EGFR (IC₅₀ = 10.12 ± 0.29 nM), hCA_IX and hCA_XII (IC₅₀ = 79 ± 1.2 nM and 58 ± 0.9 nM, respectively). Cytotoxicity assays demonstrated selective activity against cancer cells, with IC₅₀ values of 16.13 µM in MDA-MB-231 and 22.57 µM in MCF-7 cells, compared to 148.32 µM in non-cancerous Vero cells. Compared to acetazolamide, compound 14 exhibited improved selectivity for cancer cells. Apoptosis studies revealed significant cell death in MDA-MB-231 cells, with early and late apoptosis rates of 22.50% and 58.27%, respectively, alongside a marked G1-phase cell cycle arrest (49.10% in treated cells vs. 44.98% in controls). In silico toxicological evaluations indicated a favorable safety profile, with low irritancy and acceptable rat oral LD₅₀ (15.81 mg/kg) and carcinogenic potency (TD₅₀ = 36.95). Compound 14’s potent dual inhibition and selective cytotoxicity make it a promising candidate for further optimization and in vivo studies.